Governance challenges in distance education : a case study at the Centre for Open And Lifelong Learning (Coll) the Namibia University of Science and Technology (Nust) - Muundjua, Jackpelins (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.